From Community to Alienation: Psychological and Social Isolation in Mary Shelley's Frankenstein - Abdalla, Shabaz; Abdulqadir, Ayub Hasan; Ali, Zuber Osman; Ahmad, Hedayat Muhamad (LET: Linguistics, Literature and English Teaching Journal, 2024)
The theme of alienation is explored in Mary Shelley’s 'Frankenstein' as this study investigates how the narrative mirror the various intricacies of human relations and demands on society in the Victorian times. In the study, the psychological and social dimensions of alienation in Victor Frankenstein, and his creation are analysed qualitatively, using a text analysis. What the findings show is that alienation is not a matter of personal struggle but rather reflects broader moral and social struggles, including the aftermath of the Industrial Revolution and attempts to construct identity in a changing world. By providing insights into the messy nature of alienation as multifaceted phenomenon, crossing time, this study contributes to the discussion of individuality and societal dissociation, which have become topics of discussion in contemporary literature. This study therefore also has the implications that literature can contribute to the enduring human concern, and should continue to become explored in terms of alienation in historical and modern contexts.